2019
DOI: 10.3389/fonc.2019.00822
|View full text |Cite
|
Sign up to set email alerts
|

The Use of (Network) Meta-Analysis in Clinical Oncology

Abstract: Meta-analysis is important in oncological research to provide a more reliable answer to a clinical research question that was assessed in multiple studies but with inconsistent results. Pair-wise meta-analysis can be applied when comparing two treatments at once, whereas it is possible to compare multiple treatments at once with network meta-analysis (NMA). After careful systematic review of the literature and quality assessment of the identified studies, there are several assumptions in the use of meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 102 publications
(171 reference statements)
0
29
0
2
Order By: Relevance
“…Nevertheless, this therapy remains superior to placebo. The validity of these results is weakened by the network’s inconsistency, namely, by incoherence among direct and indirect estimates [ 32 ]. The main source of inconsistency is located within the closed-loop Placebo vs. SSA alone vs. Everolimus ± SSA ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this therapy remains superior to placebo. The validity of these results is weakened by the network’s inconsistency, namely, by incoherence among direct and indirect estimates [ 32 ]. The main source of inconsistency is located within the closed-loop Placebo vs. SSA alone vs. Everolimus ± SSA ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…We will first include all studies that include the use of TPE. We will then categorize the included studies using the following classifications, as reported by ter Veer et al[3]:…”
Section: Methodsmentioning
confidence: 99%
“…Finally, NMA summarizes relative treatment effects from independent trials which infers indirect treatment comparisons. However, indirect evidence should be interpreted with caution since it may be more susceptible to imbalanced stratification [81] . Notably, an important caveat when interpreting results for any meta -analyses is that historical migration (demographics, staging, and treatment techniques/systemic agents, etc.)…”
Section: Meta-analysismentioning
confidence: 99%